Process Evaluation of Nutrition Intervention Strategy in a Local Philippine Setting - Rowena V. Viajar; Julieta B. Dorado; Glenda P. Azaña; Heidenhein A. Ibarra; Eldridge B. Ferrer; Mario V. Capanzana (SAGE Publishing, 2020)
Aims: Undernutrition among 0 to 5 years old children remains a public health problem in the Philippines. This process evaluation study documented and examined the implementation of an intervention strategy for young children. Methods: Complementary feeding of 6-month to 2-year-old children was implemented for 120 days by the municipalities of Plaridel and Pulilan in Bulacan, Philippines utilizing local-based food made of rice and mung bean along with nutrition education classes among mothers/caregivers using the developed nutrition modules. A total of 121 mother-/caregiver-child pairs were the program participants of the intervention. Pre-post design were used in the analysis of quantitative data. Qualitative data were encoded verbatim manually using emerging themes. Key informant interviews among community workers and municipal officials and focus group discussions among mothers/caregivers and community workers were conducted to gather the needed data. Results: The municipalities adhered to the program phases of planning, organizing, implementation, monitoring, and evaluation. At end-line, the weight of children participants increased in both municipalities and the mean nutrition knowledge scores of mothers/caregivers increased significantly ( P < .05). Conclusions: This process evaluation confirmed that the proposed nutrition intervention strategy for young children can be implemented at the local level. The strong support and active cooperation of the local program implementers and mothers/caregivers and adherence to program requirements were the key factors in the efficient implementation of the intervention. For sustainability, the passing of local ordinance for the adoption of intervention and budget support for implementation of the intervention is recommended.